Designed Long‐Lived Emission from CdSe Quantum Dots through Reversible Electronic Energy Transfer with a Surface‐Bound Chromophore - La Rosa, Marcello (Angew Chem Int Ed Engl, 2018)
The size‐tunable emission of luminescent quantum dots (QDs) makes them highly interesting for applications that range from bioimaging to optoelectronics. For the same applications, engineering their luminescence lifetime, in particular, making it longer, would be as important; however, no rational approach to reach this goal is available to date. We describe a strategy to prolong the emission lifetime of QDs through electronic energy shuttling to the triplet excited state of a surface‐bound molecular chromophore. To implement this idea, we made CdSe QDs of different sizes and carried out self‐assembly with a pyrene derivative. We observed that the conjugates exhibit delayed luminescence, with emission decays that are prolonged by more than 3 orders of magnitude (lifetimes up to 330 μs) compared to the parent CdSe QDs. The mechanism invokes unprecedented reversible quantum dot to organic chromophore electronic energy transfer.